2021
DOI: 10.1002/bkcs.12451
|View full text |Cite
|
Sign up to set email alerts
|

Planarized B,N‐diarylated dibenzoazaborine compounds for deep blue fluorescence

Abstract: A series of planarized B,N‐diarylated dibenzoazaborine compounds (5a–5e) in which various functional groups are introduced into the B‐Ph and N‐Ph moieties of nonsubstituted dibenzoazaborine compound (I) were prepared. All compounds exhibit strong low‐energy absorptions at ca. 410–426 nm with a gradual red‐shift depending on the electron‐accepting property of the four substituents (4‐R = 4‐Ph < 4‐Pm < 4‐CNPh <4‐CN) on the B‐Ph ring in 5a–5d. Introduction of an electron‐donating tBu group into the N‐Ph ring furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…41–45 ppm, similar to those observed for A , confirmed the presence of a trigonal boron atom of the benzonaphthoazaborine skeleton. 25,29…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…41–45 ppm, similar to those observed for A , confirmed the presence of a trigonal boron atom of the benzonaphthoazaborine skeleton. 25,29…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, we recently reported a series of planarized B,N-diarylated dibenzoazaborine compounds, where various electronic modications on the B-and/or N-aryl groups were performed to control the HOMO-LUMO bandgap while preserving the dibenzoazaborine ring core (e.g., R 1 = H; R 2 = aryl in A in Chart 1). 29 Although the emission can be effectively controlled to produce deep blue uorescence at 421-439 nm, we concluded that the bandgap control by modifying the B,N-diaryl groups has a limitation, probably due to the simultaneous electronic effects of the B-or N-aryl substituents on both the HOMO and LUMO levels, partially offsetting the bandgap.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations